PERSEPSI MASYARAKAT TERHADAP RESTOCKING IKAN DI RAWA PENING, DESA KEBONDOWO, KABUPATEN SEMARANG - Wijayanto, Dian; Prastawa, Heru; Purbowati, Endang; Setyowati, Ro'fah; Dwidiyanti, Meidiana; Isnanto, R. Rizal; Wisnaeni, Fifiana; Setiadji, Bagus Hario; Kurnia, Dita Juni (Universitas Mataram, 2025)
Rawa Pening is a natural lake located in Semarang Regency that is facing issues with declining fish stock. Fish restocking activities in Rawa Pening are one of the solutions to maintain fish stock, fishermen's livelihoods, and food security. Fish restocking activities in Rawa Pening were carried out in July 2025 by the Undip community service team, involving the release of nilem and tawes fish, which are classified as local (non-invasive) species. An evaluation of local residents' perceptions of the fish restocking activities was conducted through interviews with 30 local residents who work as fishermen and fish processors. The evaluation results indicate that the fish restocking activity in Rawa Pening has received a positive response from the community service activity partners, with 100% of respondents agreeing with the restocking activity, primarily citing increased fishermen's income and maintaining fish populations in Rawa Pening as the main reasons. However, local residents' understanding and knowledge regarding the technical aspects of the restocking activity still need to be improved.